Production of light nuclei, hypernuclei and their antiparticles in relativistic nuclear collisions - Andronic, Anton; Braun-Munzinger, P.; Stachel, Johanna; Stöcker, H. (Physics letters, 2011)
We present, using the statistical model, an analysis of the production of light nuclei, hypernuclei and their antiparticles in central collisions of heavy nuclei. Based on these studies we provide predictions for the production yields of multiply-strange light nuclei.